STEREOTACTIC RADIOSURGERY FOR PATIENTS WITH MELANOMA AND MULTIPLE BRAIN METASTASES: EXPERIENCE DURING THE ERA OF IMMUNOTHERAPY AND TARGETED AGENTS. (3rd October 2018) - Sanghera, Paul; Fox, Richard; Benghiat, Helen; Meade, Sara; Hartley, Andrew; Cruickshank, Garth; Sawlani, Vijay; Steven, Neil
Abstract: There has been significant progress in the treatment of metastatic melanoma, however the impact of new agents on patients with brain metastases remains poorly understood. We report outcomes using SRS for patients with melanoma brain metastases exposed to BRAF targeted agents and/or immunotherapy. METHODS Consecutive patients with metastatic melanoma and brain metastases undergoing SRS without routine whole brain radiotherapy were identified. Selection was restricted to patients having systemic therapy within the same centre. Follow-up included 3monthly MRI scans. All patients were treated using Cyberknife. The target volume was neuroradiology approved without an uncertainty margin. A review of electronic records and follow up imaging was undertaken. Survival data were summarized using Kaplan-Meier curves and compared via a logrank test. RESULTS 49 patients with 148 target metastases were identified. Median number of lesions was 2 (range 1–12), median dose 21Gy, median volume 0.31cc (range 0.01–6.71cc) and 94% had extracranial disease at 2 or more sites. Three patients did not have follow up MRI. One patient required long-term steroids, 1 had transient symptomatic swelling at 11months and 3 patients experienced bleeds (1 symptomatic- post-SRS treated lesion). 12-month local disease free survival was 71% (CI 53, 84). Distant brain progression occurred in 28 patients (57%), with a median time to progression of 8months (95% CI 5, 15). Distant brain progression was less frequent in patients with a single metastasis (p=0.03). Median overall survival (OS) was 11months (95% CI 8, 17). Median OS was 20months (95% CI 5, NR), 10months (95% CI 4, 12) and 11months (95% CI 3, NR) for patients with 1, 2–4 and ≥ 5 metastases respectively (p=0.07). CONCLUSION Beyond a single metastasis, the number of brain metastases did not correlate with OS. Patients with multiple brain metastases and active systemic disease may benefit from SRS however prospective evaluation is recommended.